Effectiveness of Banxia Xiexin Decoction in the treatment of precancerous lesions: A protocol for systematic review and meta-analysis. Issue 16 (23rd April 2021) - Yi, Ying; Hu, Ziyi; Li, Renliang; Chen, Lisha; Zhang, Hengyi; Li, Hong; Wu, Mengwen; Liu, Wanting
Abstract: Background: Gastric precancerous lesion (GPL) is a necessary stage in the occurrence and development of gastric cancer. At present, the incidence of gastric cancer is increasing year by year. It is important to prevent and control gastric cancer through early detection and intervention. Banxia Xiexin Decoction (BXD) has a good effect in improving symptoms, reducing inflammation, promoting the repair of gastric mucosa, reversing its atrophy and intestinal metaplasia. BXD may be a foreground choice for the treatment of GPL. Methods: Randomized controlled trials of BXD for GPL will be searched in the relevant database, including PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang Database, Chinese Biomedical Literature Database (CBM), and Chinese Scientific Journal Database (VIP database). The studies of electronic searches will be exported to EndNote V.9.1 software. We will run meta-analyses using the Review Manager (RevMan) V.5.3 software. Any disagreement will be solved in consultation with a third reviewer. Results: Our study aims to explore the efficacy of BXD for GPL and to provide up-to-date evidence for clinical of GPL. Conclusion: The conclusion of this study will provide evidence for the efficacy of BXD on GPL. INPLASY registration number: INPLASY 202130102.